Influence of Type of Culture Media and Light Colors on Biomass and Harvesting Time of Green Algae (Chlorococcum humicola) - Al-temimi, Aya A.N.; Al-Akailly, Thaer M. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The current study aimed to determine the effect of exposure to different colors of light and culture media with different concentrations of nutrients on growth curves, growth rates, doubling times of Chlorococcum humicola and different harvest times. The studied algae were grown in two different media, Chu13 and BG11 for comparison purpose with the effect of three colors of white, blue, and red lights. White light was adopted as a control factor. The harvest was carried out after the days (7, 14, 21, 28, 35) days of development to determine the highest growth rate in the shortest time during five weeks and therefore to determine the best harvest time in producing the highest growth rates and growth curves and the lowest doubling time during the experiment period of 35 days by the effect of different treatments and at a temperature of (2±25)°C and a light intensity of 3000 lux and a light system of 8/16 hours of light / darkness by conducting daily measurements by reading the absorption values and calculating the number of cells for each culture medium in each light color. The results of the study showed that the highest growth rate and the least doubling time depending on the values of absorption and the number of cells was recorded in the medium BG11 when exposed to blue light at harvest on the seventh day of the experiment. The results recorded the highest growth rate based on absorbance values and cell numbers on the seventh day of the experiment in BG11 medium with the effect of blue light.